Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening pada Dinas Kependudukan dan Pencatatan Sipil Sumatera Barat - Ratu Humayroh Aldora; Ramdani Bayu Putra; Dodi Suryadi; Hasmaynelis Fitri (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to find out how much influence work motivation and work discipline have on employee performance with job satisfaction as an intervening variable at the West Sumatra Population and Civil Registration Service. Documentation methods and types of primary data.. Research results obtained based on partial tests (T tests) obtained: There is a significant positive influence between work motivation and job satisfaction at the West Sumatra Population and Civil Registration Service. With an influence of 0.007. There is an insignificant positive influence between Work Discipline on Job Satisfaction at the West Sumatra Population and Civil Registration Service. With an influence of 0.612. There is an insignificant positive influence between work motivation on employee performance at the West Sumatra Population and Civil Registration Service. With an influence of 0.188. There is an insignificant negative influence between Work Discipline on Employee Performance at the West Sumatra Population and Civil Registration Service. With an influence of 0.101. There is a significant positive influence between Job Satisfaction on Employee Performance at the West Sumatra Population and Civil Registration Service. With an influence of 0,000. There is an insignificant positive influence on Job Satisfaction mediating Work Motivation on Employee Performance at the West Sumatra Population and Civil Registration Service. With an influence of 0.040. There is an insignificant positive influence on Job Satisfaction mediating Work Discipline on Employee Performance at the West Sumatra Population and Civil Registration Service. With an influence of 0.587.